Governance and bank valuation - Caprio, Gerard; Laeven, Luc; Levine, Ross (Journal of Financial Intermediation, 2007)
This paper assesses the impact of the ownership structure of banks and shareholder protection laws on bank valuations while controlling for differences in bank regulations. Except in a few countries with very strong shareholder protection laws, banks are not widely held. Rather, families or the State control banks. Furthermore, (i) larger cash-flow rights by the controlling owner boost valuations, (ii) stronger shareholder protection laws increase valuations, and (iii) greater cash-flow rights mitigate the adverse effects of weak shareholder protection laws on valuations. These results suggest that ownership structure is an important mechanism for governing banks.